ARGUMENTATIVE APPROACHES IN THE COMMUNICATION PROCESS IN ARAB CULTURE - Ezzine Abdelhak,; Benkadour Houria, (International Journal of Innovative Technologies in Social Science, 2024)
This article seeks to define arguments in the communication process within Arab culture due to its great importance. We have examined the approaches used in the rhetorical, logical, and systematic persuasion process.